Stability of serotypes during nasopharyngeal carriage of Streptococcus pneumoniae. - Meats, E; Brueggemann, A; Enright, M; Sleeman, K; Griffiths, D; Crook, D; Spratt, BG (2003)
Serotype changes among natural isolates of Streptococcus pneumoniae are well documented and occur by recombinational exchanges at the capsular biosynthetic locus. However, the frequency with which this phenomenon occurs within the nasopharynx of children is not clear and is likely to be highest in the nasopharynx of children, who have high rates of pneumococcal carriage. A birth cohort of 100 infants was studied, and pneumococci were recovered from nasopharyngeal samples taken at monthly intervals during the first 6 months of life and then at 2-monthly intervals until the age of 2 years. Among the 1,353 nasopharyngeal samples were 523 that contained presumptive pneumococci, and three colonies from each were serotyped. A total of 333 isolates, including all isolates of differing serotypes from the same child, were characterized by multilocus sequence typing. Sixty-eight children carried multiple serotypes during the first 2 years of life. Two children carried a typeable and a nonserotypeable pneumococcus of identical genotype, and five children carried genetically indistinguishable isolates of serotypes 15B and 15C. These isolates were considered, respectively, to be due to loss of capsule expression and the known ability of serotype 15B and 15C pneumococci to interconvert by loss or gain of an acetyl group on the capsular polysaccharide. In all other cases, isolates from the same children that differed in serotype also differed in genotype, indicating the acquisition of a different pneumococcal strain rather than a change in capsular type. There was therefore no evidence in this study for any change of serotype due to recombinational replacements at the capsular locus among the pneumococci carried within the nasopharynges of the children.